The Inhibition of RNA Viruses by Amaryllidaceae Alkaloids: Opportunities for the Development of Broad‐Spectrum Anti‐Coronavirus Drugs. Issue 4 (14th January 2022) - Tan, Shen; Banwell, Martin G.; Ye, Wen‐Cai; Lan, Ping; White, Lorenzo V.
Abstract: The global COVID‐19 pandemic has claimed the lives of millions and disrupted nearly every aspect of human society. Currently, vaccines remain the only widely available medical means to address the cause of the pandemic, the SARS‐CoV‐2 virus. Unfortunately, current scientific consensus deems the emergence of vaccine‐resistant SARS‐CoV‐2 variants highly likely. In this context, the design and development of broad‐spectrum, small‐molecule based antiviral drugs has been described as a potentially effective, alternative medical strategy to address circulating and re‐emerging CoVs. Small molecules are well‐suited to target the least‐rapidly evolving structures within CoVs such as highly conserved RNA replication enzymes, and this renders them less vulnerable to evolved drug resistance. Examination of the vast literature describing the inhibition of RNA viruses by Amaryllidaceae alkaloids suggests that future, broad‐spectrum anti‐CoV drugs may be derived from this family of natural products. Abstract : The development of antiviral therapeutics based on Amaryllidaceae alkaloids may provide decisive medical solutions to catastrophic coronavirus pandemics. Since many of these compounds exert their antiviral action by targeting host‐factors, they present opportunities to develop broad‐spectrum treatments that are less susceptible to evolved drug resistance.